ILRI 40 years hard talk: Connecting agricultural science to sustainable development - International Livestock Research Institute (International Livestock Research Institute, 2014)
Brian Perry in conversation with Peter Jeffries, Sarah Jackson and Azage Tegegne. 'Hard talk' at the ILRI@40 Conference: Livestock-based options for sustainable food and nutritional security, economic well-being and healthy lives, Addis Ababa, Ethiopia, 6–7 November 2014.